The Influence Of Human Practices, Digital Intensity And Innovation On Service Recovery Performance In Malaysian Hotels - Rosli, Nuraina Nadiah (2024)
Service Recovery Performance forms an essential basis for obtaining long term success for hotel firms. Nonetheless, empirical research on this potential service recovery performance has received limited attention in hotel research. Drawing from Resource Base View (RBV) theory and Business Model Innovation (BMI) theory, this study tests a conceptual model that examines the mediating role of Service Innovation between Digital Intensity and different aspects of Human Practices on Service Recovery Performance within the hotel industry of Malaysia. This study also recognizes the importance of Innovative Culture as the boundary condition between Service Innovation and Service Recovery Performance.